Informatics Education Students' Perceptions of the Use of Edlink LMS in Data Structure Courses - Derosari, Katarina; Sogen, Maria Magdalena Beatrice; Tabala, Yudi Erwina; Aleut, Ido Yohanis (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine Informatics Education student’s perceptions of using the EdLink Learning management system (LMS) in the Data Structures course. The research employs a mix method approach, combining quantitative and qualitative data collection throughused questionnaires and interviews with students who have used EdLink during lectures. The results indicate that most students find EdLink facilitates access to learning materials, enhances communication with lecturers, and supports independent learning. However, some challenges challenges were identified include technical issues and limited interactive features. These findings are expected to provide valauable input for the further development of EdLink LMS to better support data Structures learning.